ANALISA NONLINEAR BALOK TINGGI BETON BERTULANG DENGAN MODIFIED COMPRESSION FIELD THEORY - Windah, Reky Stenly (Sam Ratulangi University, 2011)
The modified compression field theory, MCFT, an analytical model that is capable of predicting not only the shear strength but also the load-deformation response of reinforced concrete elements subjected to in-plane shear and normal stresses, such as deep beams. This rationalmodel satisfies the three fundamental principles of the mechanics of materials: stress equilibrium, strain compatibility, and the constitutive laws of materials.The accuracy of MCFT method in predicting shear strength of reinforced concrete deep beam is very good. This indicated by the value Ptest/Pmcft of 7,14 %.Keywords: the modified compression field theory, shear strength, load-deformation response, in-plane shear, deep beam.